STUDENT MOTIVATION IN CHOOSING THE ENGLISH EDUCATION MAJOR AT THE FACULTY OF TADRIS AND TARBIYAH UIN FATMAWATI SUKARNO BENGKULU BASED ON COHORT 2024 - Etika Li; Ali Akbarjono; Yashori Revola (STKIP Subang, 2025)
This study aims to explore the motivations of students in choosing the English Education major at the Faculty of Tadris and Tarbiyah, UIN Fatmawati Sukarno Bengkulu, cohort 2024, and to analyze their influence on academic achievement. This research employed a qualitative descriptive design using in-depth interviews with three students representing both male and female perspectives, supported by observations and relevant document studies. The findings reveal that student motivations differ according to gender: female students are primarily driven by intrinsic factors, such as personal interest in English, enjoyment of learning, and the aspiration to become educators, while male students tend to emphasize extrinsic factors, including career prospects, financial independence, and parental support. Some students exhibit a combination of intrinsic and extrinsic motivations, where personal interest is reinforced by external encouragement. Motivation was found to significantly impact academic achievement: intrinsic motivation fosters deep engagement, active participation, and additional learning efforts, whereas extrinsic motivation promotes goal-oriented behavior, discipline, and consistency in completing assignments. Understanding these motivational differences and their effects on academic performance is crucial for educators to design supportive learning environments that meet diverse student needs and enhance overall academic success.